You and me versus the rest of the world: the effects of affiliative motivation and ingroup partner status on social tuning - Skorinko, Jeanine Lee McHugh; John, Melissa-Sue; Doyle, Aidan; Carvajal Erker, Natalia; Figueroa, Matthew; Harnois, Jeffrey; Gately, Grace; Spear, Sarah; Marotta, Satia; McKenna, Casey; Rossi, Lisa; Heather, Kenedi; et al. (Frontiers in Psychology, 2023)
Bandura (1969) argues that individuals are more likely to engage in social learning when they identify with a social model and when they are motivated or rewarded. Therefore, in the present work, we investigate how these two key factors, perceived similarity and affiliative motivation, influence the extent to which individuals engage in social tuning or align their views with an interaction partner—especially if their partner’s attitudes differ from the larger social group. Experiment 1 explored the role of perceived similarity when needing to work collaboratively with a collaboration partner whose beliefs differed from a larger social group. Experiment 2 directly manipulated affiliative motivation along with perceived similarity. Experiments 3 and 4 replicated Experiment 2 and examined whether tuning occurred for implicit attitudes as well. Results indicate that when individuals experience high affiliative motivation, they are more likely to engage in social tuning of explicit and implicit attitudes when their interaction partner belongs to their ingroup rather than their outgroup. These findings are consistent with the tenets of Social Learning Theory, Shared Reality Theory, and the affiliative social tuning hypothesis.